Modelling the impact of climate change and atmospheric N deposition on French forests biodiversity. (June 2016) - Rizzetto, Simon; Belyazid, Salim; Gégout, Jean-Claude; Nicolas, Manuel; Alard, Didier; Corcket, Emmanuel; Gaudio, Noémie; Sverdrup, Harald; Probst, Anne
Abstract: A dynamic coupled biogeochemical–ecological model was used to simulate the effects of nitrogen deposition and climate change on plant communities at three forest sites in France. The three sites had different forest covers (sessile oak, Norway spruce and silver fir), three nitrogen loads ranging from relatively low to high, different climatic regions and different soil types. Both the availability of vegetation time series and the environmental niches of the understory species allowed to evaluate the model for predicting the composition of the three plant communities. The calibration of the environmental niches was successful, with a model performance consistently reasonably high throughout the three sites. The model simulations of two climatic and two deposition scenarios showed that climate change may entirely compromise the eventual recovery from eutrophication of the simulated plant communities in response to the reductions in nitrogen deposition. The interplay between climate and deposition was strongly governed by site characteristics and histories in the long term, while forest management remained the main driver of change in the short term. Highlights: The effects of N atmospheric deposition and climate change on vegetation were simulated. The model ForSAFE-Veg was calibrated and validated carefully for three forests in France. Climate has a greater influence on vegetation than N deposition in conifer forests. N-poor ecosystems are, however, more sensitive to N deposition than to climate change. Abstract : Compared to nitrogen atmospheric deposition, climate appears to be the main driver of change in forest plant biodiversity on a century scale, except in N-poor ecosystems.